Respuesta :

Answer:

0

Step-by-step explanation:

We have the two functions:

[tex]f(x)=\sqrt{x}+12\text{ and } g(x)=2\sqrt{x}[/tex]

And we want to find (f-g)(144).

This is the same thing to f(144)-g(144).

So, let’s determine the value of f(144) and g(144) first:

[tex]\begin{aligned} f(144)&=\sqrt{144}+12 \\ &=12+12 \\ &=24\end{aligned}[/tex]

And:

[tex]\begin{aligned} g(144)&=2\sqrt{144} \\ &=2(12) \\ &=24 \end{aligned}[/tex]

Hence:

[tex]\begin{aligned} (f-g)(144) &= f(144)-g(144) \\ &=24-24 \\ &=0 \end{aligned}[/tex]

Our final answer is 0.

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

[tex](f - g)(x) = \sqrt{x} + 12 - 2 \sqrt{x} \\ [/tex]

[tex](f - g)(x) = - \sqrt{x} + 12[/tex]

[tex](f - g)(144) = - \sqrt{144} + 12[/tex]

[tex](f - g)(144) = - \sqrt{ {12}^{2} } + 12 [/tex]

[tex](f - g)(144) = - (12) + 12[/tex]

[tex](f - g)(144) = - 12 + 12[/tex]

[tex](f - g)(144) = 0[/tex]

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️